Education for Hmong Women in Thailand - Peng, Xuefang (The Australian Journal of Indigenous Education, 2007)
Abstract The Hmong are the second largest tribal group in Thailand. Hmong society is stratified by both age and gender. Women were considered inferior to men in Hmong traditional society. There was a strong bias against education for Hmong women in the past. Hmong women’s access to education has improved with recent developments in the socio-economy and modern educational system. Today there does not appear to be discrimination against girls in continuing their education beyond the compulsory level. However, the conventional ideas that “marrying early, bearing early, and having many children are blessings” are popular in the Hmong community. Many girls of school age leave school for marriage. These traditional conventions are an obstacle for females in continuing their formal education. Today, the Hmong’s traditional subsistence economy is undergoing change, and many Hmong women are actively involved in business. Adult and vocational education is also an important way for Hmong women to improve their educational level and gain new skills for making a living. This paper is based on anthropological field research carried out in northern Thailand from December 2003 to September 2004, supported by the Asian Scholarship Foundation.